2020
DOI: 10.3390/ijms22010329
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Modulation of SP1 Functional Binding Sites at the KIT Proximal Promoter

Abstract: The regulation of conformational arrangements of gene promoters is a physiological mechanism that has been associated with the fine control of gene expression. Indeed, it can drive the time and the location for the selective recruitment of proteins of the transcriptional machinery. Here, we address this issue at the KIT proximal promoter where three G-quadruplex forming sites are present (kit1, kit2 and kit*). On this model, we focused on the interplay between G-quadruplex (G4) formation and SP1 recruitment. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
(43 reference statements)
3
17
0
Order By: Relevance
“…We showed that CTCF binds folded G4s and consensus duplexes with comparable affinities (Figure 4). This is hardly surprising, because G4 recognition has been reported previously for other zinc-finger transcription factors with G-rich binding motifs, such as Sp1 [38,39] and MAZ [40]. The latter is functionally rather similar to CTCF, and the two work together as insulators to shape topologically associating domains (TAD) and sub-TAD domains.…”
Section: Discussionmentioning
confidence: 78%
“…We showed that CTCF binds folded G4s and consensus duplexes with comparable affinities (Figure 4). This is hardly surprising, because G4 recognition has been reported previously for other zinc-finger transcription factors with G-rich binding motifs, such as Sp1 [38,39] and MAZ [40]. The latter is functionally rather similar to CTCF, and the two work together as insulators to shape topologically associating domains (TAD) and sub-TAD domains.…”
Section: Discussionmentioning
confidence: 78%
“…four ∼60 base-long oligonucleotides different in their central part (red in Figure 1 ) where the G4-forming sequences c-kit2 and c-kit* (c-kit2_TEMP and c-kit*_TEMP in Figure 1 , respectively), or their non G4-forming mutated counterparts (Blank2_TEMP and Blank*_TEMP, respectively) where inserted. The inability of the mutated sequences to form G4 is demonstrated in ( 42 ) for Blank2 and in ( 31 ) for Blank*.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, G4s are often located in promoter sequences as shown for many human genes [69][70][71], including P53 targets; in fact, the presence of G4 prone sequences has been found around P53 RE in the promoter of the P53-induced apoptotic PUMA protein [34]. Therefore, the presence and the formation of a G4 structure could be an important transcriptional regulatory element, as previously observed in various organisms including humans [72][73][74].…”
Section: Discussionmentioning
confidence: 63%